2023
DOI: 10.1002/csc2.20872
|View full text |Cite
|
Sign up to set email alerts
|

Salinity responses in 24 guar genotypes are linked to multigenic regulation explaining the complexity of tolerance mechanisms in planta

Abstract: Guar (Cyamopsis tetragonoloba (L.) Taub.) is an economically important, droughttolerant legume crop affected by moderate to high salinity. Guar has various industrial applications, including gum extracted from seeds that is widely used in the oil and natural gas industries. In this investigation, we evaluated the salinity tolerance of different guar genotypes and their relation to genetic mechanisms regulating guar responses to salinity stress. We screened 24 guar genotypes in a greenhouse lysimeter system und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Conversely, barley shows no yield loss with EC e = 8 dS m −1 , a 25% yield loss with EC e = 13 dS m −1 , and a 50% yield loss with EC e = 17 dS m −1 ( Amacher et al., 2000 ). It should also be noted that the salinity tolerance level of different cultivars of a specific species to salinity may show variation in responses and yields as observed in guar, alfalfa, and other crops ( Sandhu et al., 2017 ; Kaundal et al., 2021 ; Sandhu et al., 2021 , Sandhu et al, 2023 ).…”
Section: Salinity Stress In Plants and Its Impact On Crop Production ...mentioning
confidence: 99%
“…Conversely, barley shows no yield loss with EC e = 8 dS m −1 , a 25% yield loss with EC e = 13 dS m −1 , and a 50% yield loss with EC e = 17 dS m −1 ( Amacher et al., 2000 ). It should also be noted that the salinity tolerance level of different cultivars of a specific species to salinity may show variation in responses and yields as observed in guar, alfalfa, and other crops ( Sandhu et al., 2017 ; Kaundal et al., 2021 ; Sandhu et al., 2021 , Sandhu et al, 2023 ).…”
Section: Salinity Stress In Plants and Its Impact On Crop Production ...mentioning
confidence: 99%
“…Recent studies by B. Acharya et al (2022) and D. Sandhu et al (2022) have shown that guar gum can be produced at lower prices than imported gums and produce lower greenhouse gas emissions than existing crops. Given the widespread use of guar and its products in the national economy and the high purchase prices, Ukraine should not be dependent on its imports, considerably saving currency assets.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that guar gum can be produced at lower prices than US import prices and produce lower greenhouse gas emissions than existing crops in the Southwest US [8]. Salinity tolerance of guar genotypes is another advantage that can improve its adaptability in the Southwest US [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its potential as an alternative crop in the Southwest US and a renewed interest in guar production, research on various aspects of guar production has recently gained impetus in the Southwest US [9][10][11][12][13][14][15][16][17]. A few recent studies have focused on the response of guar to irrigation level and shown the adaptability of guar under deficit irrigation conditions [18,19].…”
Section: Introductionmentioning
confidence: 99%